The Story of the Teapot in DHTML. - BECKMAN, BRIAN; MEIJER, ERIK (Communications of the ACM, 2013)
The article discusses the potential use of programming languages and programmable systems to accomplish tasks outside of their original applications, focusing on the rendering of a teapot with the HTML and CSS programming languages as of March 2013. According to the article, the work of the web developer Jeff Lau with logarithmic, quadratic, and linear performance models enables the creation of the rendering. Topics include the process of creating arbitrary triangles and polygons, texture mapping, and the JavaScript language.